Health and the Economy in the United States from 1750 to the Present - Costa, Dora L. (Journal of Economic Literature, 2015)
I discuss the health transition in the United States, bringing new data to bear on health indicators, and investigating the changing relationship between health, income, and the environment. I argue that scientific advances played an outsize role and that health improvements were largest among the poor. Health improvements were not a precondition for modern economic growth. The gains to health are largest when the economy has moved from "brawn" to "brains" because this is when the wage returns to education are high, leading the healthy to obtain more education. More education may improve use of health knowledge, producing a virtuous cycle.